2015
DOI: 10.4236/nm.2015.63016
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Distal Sensory Polyneuropathy among Diabetics in Parakou in 2012

Abstract: Background: The distal sensory polyneuropathy (DSP) was more frequent among diabetics, although its determinant was not well known among diabetics in Benin. Objective: We aimed to assess the frequency of DSP and its determinants among diabetics at Parakou. Methods: It was a cross-sectional study carried out from 1 March to 31 August 2012 and included 336 diabetics followed at the diabetes unit of Parakou hospital. The diagnosis of DSP was based on DNS (Diabetic Neuropathy Score) criteria and other criteria. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
(14 reference statements)
3
1
2
Order By: Relevance
“…Similar findings were observed in studies conducted in Brazil and India [25, 26], However no such association was observed in other studies conducted in India, Iran, Benin, Taiwan [10, 14, 20, 21] The reason behind might be physical exercise can increase micro-vascular circulation, prevent aging, boosts immune system, gives strength to muscle and cardiovascular system as well as physiological well-being of the body so as to negatively affect the occurrence of DPSN.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Similar findings were observed in studies conducted in Brazil and India [25, 26], However no such association was observed in other studies conducted in India, Iran, Benin, Taiwan [10, 14, 20, 21] The reason behind might be physical exercise can increase micro-vascular circulation, prevent aging, boosts immune system, gives strength to muscle and cardiovascular system as well as physiological well-being of the body so as to negatively affect the occurrence of DPSN.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings were also lower than the study done in USA (66.7%), Benin (88.7%) and Taiwan (71%) [1921]. The differences in prevalence could possibly be due to differences in outcome tool and patient characteristics.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations